Identification of carbon-based black pigments in four South American polychrome wooden sculptures by Raman microscopy - Tomasini, Eugenia Paula (2015)
Introduction: Carbon-based pigments are a group of dark-colored materials, which are classified according to the starting material used and their manufacturing process. Raman spectroscopy is an ideal technique for the identification of carbonaceous matter. Carbon-based pigments show broad bands between 1,300 and 1,600 cm−1 but they differ in position, width and relative intensity, allowing discrimination between them. The aim of the present study was the identification of carbon-based pigments in four polychrome wooden sculptures from the Jesuit Mission La Trinidad in Paraguay. Results: Analysis of the Raman spectral parameters of the polychrome samples and comparison with those of carbon-based pigment references allowed the identification of wood charcoal, lampblack, bistre and a black earth pigment. Complementary analysis by infrared spectroscopy and elemental analysis supported the assignments. Conclusions: In this study we have provided new evidence that Raman microscopy is a powerful technique for the discrimination of carbon-based pigments in works of art. This is the first time that bistre, lampblack and a black earth pigment are identified in colonial art. The chemical information obtained on the black pigments contributed to increase our knowledge on available resources and technology used in the manufacture of the polychrome sculptures at the Jesuit Mission. This information is relevant for our studies on Colonial art.